Rattus xanthurus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
693. North-eastern Xanthurus Rat Rattus xanthurus French: Rat & queue jaune / German: Nordostliche Gelbschwanzratte / Spanish: Rata de cola dorada nororiental Other common names: Yellow-tailed Forest Rat, Yellow-tailed Rat Taxonomy. Mus xanthura [sic] Gray, 1867, “North Celebes [= north Sulawesi, Indonesia]; Tondano . 3600 feet [= 1069 m].” Rattus xanthurusis in the R. xanthurus species group along with R. marmosurus, R. salocco, R. bontanus, and R. pelurus, although taxo-nomic affinities of this group are not well known; the group is probably sister to the Recent New Guinea and Australian clade (leucopus / fuscipes and New Guinea species groups). Rattus xanthurus might represent multiple species, and the entire R. xanthurus species group is currently under revision. Distribution. NE part of the N peninsula of Sulawesi. Descriptive notes. Head—body 235-260 mm, tail 293-330 mm, hindfoot 45-48 mm. No specific data are available for weight. The North-eastern Xanthurus Rat is large, with harsh long pelage, long black guard hairs, and black spines, extending onto base of tail. Dorsum is yellow grayish brown, washed with yellow and black, being somewhat lighter on sides. Venteris lighter than dorsum but generally yellow grayish brown. Feet are dark brown and haired dorsally. Tail is ¢.125% of head—body length and black for basal one-third and yellow for the rest. Skull has small teeth, large bulla, and large foramina. Nematodes (Syphacia sulawesiensis and S. mauris), various species of Odilia, and some ticks have been recorded from the North-eastern Xanthurus Rat. There are three pairs of mammae: one pectoral and two inguinal. Chromosomal complement is 2n = 42; FN = 59 (males) or 60 (females). Habitat. [.owland tropical evergreen moist forest at elevations below 1000 m. Northeastern Xanthurus Rats have been found in cacao agroforest systems. Food and Feeding. North-eastern Xanthurus Rats are frugivorous. Breeding. No information. Activity patterns. North-eastern Xanthurus Rats are probably nocturnal, and ...